Bakery yeasts, a new model for studies in ecology and evolution. Issue 11 (25th September 2018) - Carbonetto, Belén; Ramsayer, Johan; Nidelet, Thibault; Legrand, Judith; Sicard, Delphine
Abstract: Yeasts have been involved in bread making since ancient times and have thus played an important role in the history and nutrition of humans. Bakery‐associated yeasts have only recently attracted the attention of researchers outside of the bread industry. More than 30 yeast species are involved in bread making, and significant progress has been achieved in describing these species. Here, we present a review of bread‐making processes and history, and we describe the diversity of yeast species and the genetic diversity of Saccharomyces cerevisiae isolated from bakeries. We then describe the metabolic functioning and diversity of these yeasts and their relevance to improvements in bread quality. Finally, we examine yeast and bacterial interactions in sourdoughs. The purpose of this review is to show that bakery yeast species are interesting models for studying domestication and other evolutionary and ecological processes. Studying these yeasts can contribute much to our fundamental understanding of speciation, evolutionary dynamics, and community assembly, and this knowledge could ultimately be used to adjust, modify, and improve the production of bread and the conservation of microbial diversity. Abstract : Bread is found worldwide, and its history is well documented; the bread production process is easily replicated, and dough can be easily sampled; Saccharomyces cerevisiae is the best known yeast species; the genomes of several non‐ Saccharomyces bakery yeasts species have been recently sequenced or soon will be; sourdough microbial communities are relatively simple, and sourdough community members can be easily isolated and grown in lab conditions. Taking these reasons into account, we can state that sourdough bread is an appealing system to study the ecological and evolutionary processes underlying yeast diversity.